Effects of the Management Control System on Empowerment and Organizational Resilience - Ilse Maria Beuren; Vanderlei dos Santos; Daniele Cristina Bernd (BBR: Brazilian Business Review)
The aim of this study is to examine the effects of the enabling perception of the Managerial Control System (MCS) on psychological empowerment and organizational resilience. A survey was conducted with 161 managers of Brazilian companies that had undergone the process of acquiring another company and a structural model was developed to answer the hypotheses of the research. The results show that the enabling perception of MCS is associated with psychological empowerment and capacity for organizational resilience, which indicates that the characteristics of the MCS affect managers’ motivation regarding their work environment and contribute to companies dealing effectively with adversities and contingencies. MCSs help organizations in the process of absorbing changes and regaining balance after some temporary disruption, as in the case of acquiring other companies. It is concluded that enabling MCSs favors the empowerment of managers and supports companies in dealing more effectively with the turbulence to which they are exposed.